(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper deals with the “Rights of arrested and accused person in India”. This article is based upon the norms of the criminal law is that the “thousand accused can punished but one innocent shouldn’t be punished”. The paper would like to explicit that One of the basic tenets of our legal system is the benefit of the presumption of innocence of the accused till he is found guilty at the end of a trial on legal evidence in a democratic society even the rights of accused are sacrosanct, the accused in India are afforded certain rights, the most basic of which are found in the Indian constitution. Hope the paper provides an advanced on rights of arrested and accused person in India.